FORMULASI SEDIAAN FACIAL WASH GEL EKSTRAK ETANOL DAUN AFRIKA (Vernonia amygdalina Del) SEBAGAI PELEMBAB - Chandra, Devina; Lifiani, Rialita; Bemby Sinaga, Arman; Wilson Sembiring, Antonius (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
African leaves (Vernonia amygdalina Del) contain flavonoids that can provide antioxidant effectiveness fromflavonoids and also contain vitamins C and E. And its function is to neutralize free radicals. The purpose of this study was to formulate facial wash gel preparations from African leaf extract, as well as to identify and test the safety, quality, and benefits of the formulation preparations. This research method was carried out experimentally. African leaf ethanol extract was obtained by maceration using 96% ethanol extract which was then concentrated with a rotary evaporator at a temperature of 40oC, then formulated in facial wash gel preparations with concentrations of 1% (Formula 1), 3% (Formula 2), and 6% (Formula 3). Evaluation of facial wash gel preparations included organoleptic examination, pH test, homogeneity, stability, viscosity, spreadability, and foaming power. Irritation test and effectiveness test using a skin analyzer on the volunteer's facial skin, the parameters measured included water content and pore size, the treatment was carried out for 4 weeks. The results of this study indicate that the evaluation of facial wash gel preparations is well formulated and stable, African leaf extract is formulated as a facial wash gel that can provide effectiveness on the volunteer's facial skin, namely increasing moisture on the skin and decreasing pore size on the volunteer's facial skin for 4 weeks of use.